2015
DOI: 10.1063/1.4906590
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of transverse-magnetic deep-ultraviolet stimulated emission from AlGaN multiple-quantum-well lasers grown on a sapphire substrate

Abstract: We demonstrate transverse-magnetic (TM) dominant deep-ultraviolet (DUV) stimulated emission from photo-pumped AlGaN multiple-quantum-well lasers grown pseudomorphically on an AlN/sapphire template by means of photoluminescence at room temperature. The TM-dominant stimulated emission was observed at wavelengths of 239, 242, and 243 nm with low thresholds of 280, 250, and 290 kW/cm2, respectively. In particular, the lasing wavelength of 239 nm is shorter compared to other reports for AlGaN lasers grown on foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 20 publications
(32 reference statements)
2
36
0
Order By: Relevance
“…[ 9–11 ] In contrast, however, the development of AlGaN‐based deep UV lasers is much slower, and the majority studies focus on optically pumped AlGaN QW lasers. [ 12–17 ] It is not until very recently that the electrically pumped AlGaN QW deep UV laser operating at 271.8 nm was achieved, [ 18 ] after the clamping of the lasing wavelength at 336 nm for more than one decade. [ 19,20 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 9–11 ] In contrast, however, the development of AlGaN‐based deep UV lasers is much slower, and the majority studies focus on optically pumped AlGaN QW lasers. [ 12–17 ] It is not until very recently that the electrically pumped AlGaN QW deep UV laser operating at 271.8 nm was achieved, [ 18 ] after the clamping of the lasing wavelength at 336 nm for more than one decade. [ 19,20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Due to the direct and appropriate bandgap energy, III‐nitrides are suitable semiconductor materials for DUV lasers. Recently, low‐threshold optically pumped edge‐emitting lasers based on III‐nitrides have been demonstrated, which is an important milestone towards realization of electrical‐driven edge‐emitting laser diodes .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] This extremely low g EQE can mainly be attributed to the material challenges including high dislocation densities (10 10 cm À2 in AlN and AlGaN layers) 10,11 and relatively low electrical conductivity in p-and n-type AlGaN cladding layers, [12][13][14][15][16][17] as well as the physics challenges such as a severe valence band-mixing effect in conventional AlGaN QW structures. [18][19][20][21][22] Specifically, previous studies revealed that the crystalfield split-off (CH) subband is dominant in the valence band for high Al-content (>68%) AlGaN QWs, which results in dominant transverse-magnetic (TM)-polarized emission at k $ 220-230 nm. 18 However, with the decrease in the Al-content, the heavy hole (HH) subband gradually moves toward the highest energy level in the valence band and causes the corresponding transition from the conduction band to the heavy hole subband (C-HH) to mix with C-light hole (LH) and C-CH transitions at k $250-300 nm.…”
mentioning
confidence: 99%